Simultaneously intensified plasmonic and charge transfer effects in surface enhanced Raman scattering sensors using an MXene-blanketed Au nanoparticle assembly. Issue 6 (14th January 2022) - Yoo, Seong Soo; Ho, Jeong-Won; Shin, Dong-In; Kim, Minjun; Hong, Sunghwan; Lee, Jun Hyuk; Jeong, Hyeon Jun; Jeong, Mun Seok; Yi, Gi-Ra; Kwon, S. Joon; Yoo, Pil J.
Abstract : MXene-blanketed Au nanoparticle assembly with energy level alignment effectively facilitates the charge transfer effect while securing the electromagnetic effect by guiding the analyte near to hotspot center for surface enhanced Raman scattering. Abstract : Surface enhanced Raman spectroscopy (SERS) is an ultrasensitive tool for detecting a wide range of analytes. The signal amplification is generally attributed to two different mechanisms, localized surface plasmonic resonance (LSPR) and short-range charge transfer (CT) effect between the analyte molecule and the surface of the substrate. Therefore, an assembly of metallic nanoparticles (NPs) has been employed as a basic SERS substrate. Conventional approaches based on metallic NPs for the SERS platform, however, have limitations in simultaneously eliciting both mechanisms as the energy level of most analytes is not aligned with the Fermi level of the metallic surface. Herein, this study presents the development of an ultrasensitive SERS platform utilizing a two-dimensional (2D) assembly of Au NPs conformally coated with a few-atom-thick MXene layer. The MXene layer enables the Fermi level of the substrate to be located between the HOMO and LUMO levels of analytes, thus efficiently facilitating the CT effect. In addition, wrinkled surface structures generated from conformal blanketing of the MXene layer over the Au NP assembly would help to increase the EM effect by guiding the analyte to be captured near the hotspot center between Au NPs. Thanks to this unique structural design using MXene layer deposition, the presented SERS platform exhibits a large analytical enhancement factor up to 1.6 × 10 10 . Furthermore, it is proven to detect Cr(vi ) with a low detection limit down to 13 ng L −1 . Therefore, the present SERS platform can be generalized and extended for quantitative detection of a wide range of analytes including molecules of interest in biomedical and environmental aspects.